Sources of financing the general budget in Algeria and challenges of its sustainability in light of the spread of the Corona pandemic - Sari, Ismail (Dirassat Journal Economic Issue, 2022)
This study aims to control the main sources of public budget financing in Algeria and the main challenges to the sustainability of public finances, in particular with regard to the spread of the Corona pandemic. We relied on the descriptive analytical approach, in order to describe the study variables and to collect and analyze the data. We had difficulty in getting the State to pursue its spending policy at the same pace given the fragility of the current financial situation with the exposure of the budget and the economy to crude oil prices. This forces the government to reform the weaknesses of the public budget in a reliable, efficient and effective manner, with the aim of reducing the cost of revenue collection and broadening its base, and facilitating the disbursement of expenditure within a framework of transparency. and discipline while reducing the cost of fiscal policy programs in order to achieve financial sustainability.